Estimates of N2O Emissions and Mitigation Potential from a Spring Maize Field Based on DNDC Model - Hu LI; Jian-jun QIU; Li-gang WANG; Ming-yi XU; Zhi-qiang LIU; Wei WANG (Journal of Integrative Agriculture, 2012)
Agricultural production plays an important role in affecting atmospheric nitrous oxide (N2O) concentrations. Field measurements were conducted in Dalian City, Liaoning Province in Northeast China from two consecutive years (2009 and 2010) to estimate N2O emissions from a spring maize field, a main cropping system across the Chinese agricultural regions. The observed flux data in conjunction with the local climate, soil and management information were utilized to test a process-based model, DeNitrification-DeComposition (DNDC), for its applicability for the cropping system. The validated DNDC was then used for exploring strategies to reduce N2O emissions from the target field. The results showed that the major N2O pulse emissions occurred with duration of about 3-5 d after fertilizer application in both years 2009 and 2010, which on average accounted for about 60% of the total N2O emissions each year. Rainfall and fertilizer application were the major factors influencing the N2O emissions from spring maize field. The average N2O fluxes from the CK (control plot, without fertilization) and FP (traditional chemical N fertilizer) treatments were 23.1 and 60.6 μg m−2 h−1 in 2009, respectively, and 21.5 and 64.3 μg m−2 h−1 in 2010, respectively. The emission factors (EFs) of the applied N fertilizer (270 kg N ha−1) as N2O-N were 0.62% in 2009 and 0.77% in 2010, respectively. The comparison of modeled daily N2O emission fluxes against observations indicated that the DNDC model had a good performance even if without adjusting the internal parameters. The modeled results showed that management practices such as no-till, changing timing or rate of fertilizer application, increasing residue incorporation, and other technically applicable measures could effectively reduce N2O emissions from the tested fields. Our study indicated that avoiding application of N fertilizers at heavy rainfall events or splitting the fertilizer into more applications would be the most feasible approaches to reduce N2O emissions from spring maize production in Northeast China.